2011
DOI: 10.1055/s-0030-1250152
|View full text |Cite
|
Sign up to set email alerts
|

Endostar, a Recombined Humanized Endostatin, Inhibits Lymphangiogenesis and Lymphatic Metastasis of Lewis Lung Carcinoma Xenograft in Mice

Abstract: Endostar significantly inhibits the lymphatic tumor growth, lymphangiogenesis and lymphatic metastasis of Lewis lung carcinoma xenografts, and its inhibitory effect is due to its ability to partially regulate the tumor expression of VEGF-C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In addition, this hypothesis is also supported by our previous studies demonstrating that delivery of exogenous TGF-␤1 to tail wounds markedly delays lymphatic repair and worsens tail edema (11). For example, endostatin treatment has been shown to decrease lung tumor metastasis in mice (13), decrease lymph node metastasis (15), and decrease lymphangiogenesis (8,28). More importantly, we found that the expression of anti-lymphangiogenic cytokines was markedly increased in the distal tail tissues harvested from wild-type animals compared with that of nude animals.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, this hypothesis is also supported by our previous studies demonstrating that delivery of exogenous TGF-␤1 to tail wounds markedly delays lymphatic repair and worsens tail edema (11). For example, endostatin treatment has been shown to decrease lung tumor metastasis in mice (13), decrease lymph node metastasis (15), and decrease lymphangiogenesis (8,28). More importantly, we found that the expression of anti-lymphangiogenic cytokines was markedly increased in the distal tail tissues harvested from wild-type animals compared with that of nude animals.…”
Section: Discussionsupporting
confidence: 58%
“…Researchers have focused on hot-spots of treating carcinoma by inhibition or destroying of tumor lymphatic tube formation early, i.e., lymphangiogenesis (9,10,18). These lymphangiogenic inhibitors such as deguelin, endostar, silencing Id-1, liposomal honokiol, mF4-31C1, Ki23057, sVEGFR3-Ig, VEGFR31-Ig, artemisinin, etodolac, MMI270, CSDA and AZM475271 have been reported as adjuvant anti-lymphangiogenic and anti-tumor drugs against some metastatic cancers in experimental and in clinical setting (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). NCTD has been reported to possess potent anti-angiogenesis and antitumor properties in several cell lines and tumor models (11)(12)(13)(14)(15)(16)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have previously reported that endostatin exerts antiangiogenic effects by blocking vascular endothelial growth factor (VEGF)-induced tyrosine phosphorylation of KDR/Flk-1 of endothelial cells (21). Dong et al (22) and Brideau et al (23) found that endostatin inhibits lymphangiogenesis by downregulating the tumor expression of VEGF-C. By contrast, the osteopontin-related mechanism may be mediated in endostatin antitumor activity (24). These data indicate that endostatin remains to be adequately elucidated.…”
Section: Discussionmentioning
confidence: 99%